Development of strategies to support home-based exercise adherence after stroke: a Delphi consensus. Issue 1 (6th January 2022) - Mahmood, Amreen; Deshmukh, Anagha; Natarajan, Manikandan; Marsden, Dianne; Vyslysel, Glade; Padickaparambil, Sebastian; TS, Shwetha; Direito, Artur; Kumaran, Senthil; N, Girish; Sachdev, Harpreet; Kumar Veluswamy, Sundar; et al.
Abstract : Objective: To develop a set of strategies to enhance adherence to home-based exercises after stroke, and an overarching framework to classify these strategies. Method: We conducted a four-round Delphi consensus (two online surveys, followed by a focus group then a consensus round). The Delphi panel consisted of 13 experts from physiotherapy, occupational therapy, clinical psychology, behaviour science and community medicine. The experts were from India, Australia and UK. Results: In round 1, a 10-item survey using open-ended questions was emailed to panel members and 75 strategies were generated. Of these, 25 strategies were included in round 2 for further consideration. A total of 64 strategies were finally included in the subsequent rounds. In round 3, the strategies were categorised into nine domains—(1) patient education on stroke and recovery, (2) method of exercise prescription, (3) feedback and supervision, (4) cognitive remediation, (5) involvement of family members, (6) involvement of society, (7) promoting self-efficacy, (8) motivational strategies and (9) reminder strategies. The consensus from 12 experts (93%) led to the development of the framework in round 4. Conclusion: We developed a framework of comprehensive strategies to assist clinicians in supporting exercise adherence among stroke survivors. It provides practical methods that can be deployed in both research and clinical practices. Future studies should explore stakeholders' experiences and the cost-effectiveness of implementing these strategies.